Sideritis raeseri-Modified Coatings on Ti-6Al-4V as a Carrier for Controlled Delivery Systems of Active Substances - Niziołek, Karina; Słota, Dagmara; Sadlik, Julia; Kosińska, Edyta; Korzeń, Klaudia; Jampilek, Josef; Sobczak-Kupiec, Agnieszka (Materials (Basel, Switzerland), 2024)
The search for the ideal metallic material for an implant is still a difficult challenge for scientists due to the phenomenon of corrosion and the consequent disruption of the implant structure. Prevention is the application of coatings that protect the implant, activate the tissues for faster regeneration, and also prevent inflammation through antibacterial and antiviral effects. The present study focuses on the selection of components for a Ti-6Al-4V alloy coating. These days, researchers are taking an intense interest in extracts of natural origin. It was decided to take a look at Sideritis raeseri, which contains vitamins and valuable elements and is rich in polyphenols, as well as antioxidants. The composition of coatings based on a PEG polymer reinforced with brushite and the S. raeseri extract with the proteins L-carnosine, fibroin, or sericin was developed. The samples were subjected to detailed physiochemical analysis, including potentiometry and electrical conductivity analysis, Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis, and UV-VIS spectroscopy. The study demonstrated that polyphenols were successfully released from the coatings during incubation in vitro. The osteointegration process can be supported by a number of factors, such as the release of polyphenols from implant coatings to prevent bacterial, viral, and fungal infections. Subjecting the samples to 14 days of incubation demonstrated their interactions with the incubation fluids, an ion exchange between the medium and the materials. An analysis of the surface morphology exhibited the presence of brushite crystals and their increased number after incubation, indicating the bioactivity of the formed coatings.
Keywords: metallic coatings; ceramics; flavonoids; polymers; composite; drug delivery system